2012
DOI: 10.4028/www.scientific.net/amm.232.730
|View full text |Cite
|
Sign up to set email alerts
|

Study of Induction Heating Process Applied to Internal Gear Using 3D Model

Abstract: The current paper is principally dedicated to the study of geometry and frequency effects for internal spur gears heated by induction. The overall work is realized by the simulation efforts performed on Comsol multi-physics software. The 3D model used during this study is built basing on coupling between Maxwell’s and heat transfer equations. This model is used to calculate the temperature profile in the gear in function of machine parameters. The module and the frequency are varied to determinate their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This mesh contains 335,024 elements and 838,747 degrees of freedom. A parallel study showed that it is necessary to keep the actual geometry of the coil instead of a simplified rectangular section [7][8].Fig. 1 shows the distributions of the induced current density and temperature after 0.5 s in the MF case(10 kHz).…”
Section: Table 1 Electromagnetic and Thermal Properties Electromagnet...mentioning
confidence: 99%
“…This mesh contains 335,024 elements and 838,747 degrees of freedom. A parallel study showed that it is necessary to keep the actual geometry of the coil instead of a simplified rectangular section [7][8].Fig. 1 shows the distributions of the induced current density and temperature after 0.5 s in the MF case(10 kHz).…”
Section: Table 1 Electromagnetic and Thermal Properties Electromagnet...mentioning
confidence: 99%
“…The first one consists in using practical trial and error methods to find the optimal process parameters, while the other consists in using simulation efforts to try to predict hardness profiles or compressive residual stress patterns. The model developed by simulation should take into account the influence of machine parameters (such as frequency, current, and heating time), material properties, coil characteristics, and part geometry [3][4].Generally, to treat gear by induction heating process, there are two major concepts. The first one is a two-step process (sequential heating process) consisting in applying a medium frequency (MF) flash which is supposed to distribute heat at the tooth root, followed by a high frequency (HF) flash to austenitize the part and generate the hardness profile upon quenching.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is a two-step process (sequential heating process) consisting in applying a medium frequency (MF) flash which is supposed to distribute heat at the tooth root, followed by a high frequency (HF) flash to austenitize the part and generate the hardness profile upon quenching. The second principal consists in a single heating step, which consists of applying simultaneously MF and HF flashes to generate heat at the tip and at the root to achieve the desired hardness profile [1,[2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The case depth is characterized by the first zone called hard zone. In fact, a case depth being at full hardness is interesting to consider as a specification since there would be a homogeneous microstructure, nearly uniform hardness, and compressive residual stresses levels [11].…”
Section: Prediction Of the Hardened Profilementioning
confidence: 99%